Chemical composition, adulteration, total microbial load, and heavy metal in raw milk samples collected from dairy farms and urban areas in Lahore District, Pakistan. Issue 1 (6th November 2019) - Arif, Atta M.; Javed, Imran; Ayaz, Muhammad; Abdullah, Muhammad; Imran, Muhammad; Rashid, Anjum; Shahbaz, Muhammad; Gondal, Tanweer A.; Qaisarani, Tahira B.; Iqbal, Zafar; Salehi, Bahare; Sharifi‐Rad, Javad; et al.
Abstract: The present study evaluated raw milk samples from dairy farms and urban areas in Lahore District, Pakistan, for the measurement of chemical composition, presence of adulterants, total microbial, and heavy metals loads. Measurements of chemical composition and physicochemical properties of the raw milk samples collected from urban areas showed the following mean values of 2.76 ± 0.29, 2.62 ± 0.18, 1.27 ± 0.08, 7.13 ± 0.30, 6.46 ± 0.26, and 0.47 ± 0.02 for lactose, fat, protein, total solids, pH, and ash, respectively, while milk samples collected from dairy farms achieved the mean values of 4.82 ± 0.32, 5.02 ± 0.39, 3.36 ± 0.18, 13.19 ± 0.66, 6.67 ± 0.27, and 0.75 ± 0.05 for lactose, fat, protein, total solids, pH, and ash, respectively. Mean values of total plate count were 5.21 ± 0.28 CFU/ml for urban areas raw milk samples and 4.67 ± 0.27 CFU/ml for the dairy farm milk samples. Heavy metal mean concentrations for Pb, Cd, Cu, Zn, and Ni in urban areas milk samples from milk shop were 0.024 ± 0.005, 0.021 ± 0.006, 1.22 ± 0.25, 2.42 ± 0.57, and 0.044 ± 0.006 ppm, respectively. Conclusively, strategies should be adopted in order to prevent the heavy metal contamination in milk to further minimizes the health risks associated with heavy metal consumption.